STUDENTS’ PERCEPTION OF USING VIDEO DUBBING TECHNIQUE FOR SPEAKING SKILL IN GUANG MING SEVENT GRADE JUNIOR HIGH SCHOOL JAMBI - Evant Danamaya Liekas (Universitas Batanghari Jambi, 2022)
This present study investigated the Students Perception of Using Video Dubbing Technique for Speaking Skill in Guang Ming Seventh Junior High School. Furthermore, it aimed to know How are the students’ perception in learning speaking skill by using video dubbing technique. This research is using qualitative method and phenomenology approach. The data analysis in this research are the interview protocol which use purposive sampling to gather the data. The research findings highlighted the following themes. Themes related to students’ experiences in learning Speaking by using Video Dubbing Technique. The finding showed that the students feel fun in learning Speaking. Video Dubbing makes learning more efficient in terms of time use. The students stated that video dubbing technique is an Interesting Method to learning speaking. And also by using video dubbing technique the students stated that using this method made the learning more fun and no time consuming.